Rotating cell culture system-induced injectable self-assembled microtissues with epidermal stem cells for full-thickness skin repair - Zhang,Min; Huang,Meng; Dong,Xixi; Wang,Yibo; Zhang,Luyue; Wang,Zhaoxiang; Cao,Junkai (PeerJ, 2024)
Epidermal stem cells (EpSCs) are crucial for wound healing and tissue regeneration, and traditional culture methods often lead to their inactivation. It is urgent to increase the yield of high quality EpSCs. In this study, primary EpSCs were isolated and cultured in a serum-free, feeder-free culture system. EpSCs are then expanded in a dynamic 3D environment using a rotating cell culture system (RCCS) with biodegradable porous microcarriers (MC). Over a period of 14 days, the cells self-assembled into microtissues with superior cell proliferation compared to 3D static culture. Immunofluorescence and qPCR analyses consistently showed that the stemness of the 3D microtissues was preserved, especially the COL17A1 associated with anti-aging was highly expressed in RCCS induced microtissues. In vivo experiments demonstrated that the group treated with 3D microtissues loaded with EpSCs showed enhanced early wound healing, and the injectable 3D microtissues were more conducive to maintaining cell viability and differentiation potential. Our study provides valuable insights into the dynamic 3D culture of EpSCs and introduces an injectable therapy using 3D microtissues loaded with EpSCs, which provides a new and effective approach for cell delivery and offering a promising strategy for guiding the regeneration of full-thickness skin defects.
Keywords: Full-thickness skin defects; Epidermal stem cells; Rotating cell culture system; Biodegradable microcarrier; Microtissues